International history of the twentieth century and beyond - Best, Antony 1964; Hanhimäki, Jussi M. 1965; Maiolo, Joseph A.; Schulze, Kirsten E. (Routledge/Taylor & Francis Group, 2015)
"This hugely successful global history of the twentieth century is written by four prominent international historians for first-year undergraduate level and upward. Using their thematic and regional expertise, the authors have produced an authoritative yet accessible and seamless account of the history of international relations in the last century, covering events in Europe, Asia, the Middle East, Africa and the Americas. They focus on the history of relations between states and on the broad ideological, economic and cultural forces that have influenced the evolution of international politics over the past one hundred years"